Interplay between menin and Dnmt1 reversibly regulates pancreatic cancer cell growth downstream of the Hedgehog signaling pathway. Issue 1 (1st January 2016) - Cheng, Peng; Wang, Yun-feng; Li, Gang; Yang, Sheng-sheng; Liu, Che; Hu, Hao; Jin, Gang; Hu, Xian-gui
Highlights: Menin inhibits pancreatic cancer cell growth in vitro and in vivo . Menin activates the expression of p18 and p27, accompanied by a decrease in DNA methylation levels of p18 and p27 promoters. Menin interacts with Dnmt1 to competitively pull down Dnmt1 from p18 and p27 promoters. Abstract: Menin, the product of the Men1 gene, which is frequently mutated in pancreatic neuroendocrine tumors, acts as a chromatin-remodeling factor to modulate the transcription of cell cycle regulators by interacting with histone modification factors. However, the function of menin and its underlying mechanisms in pancreatic ductal adenocarcinoma remain unknown. Here, we found that menin inhibited pancreatic cancer cell growth in vitro and in vivo and that its expression was gradually lost during pancreatic carcinogenesis. Menin overexpression significantly activated the expression of the cyclin-dependent kinase (CDK) inhibitors p18 and p27, accompanied with a decrease in DNA methylation levels of p18 and p27 promoters. Mechanistically, we found that interaction of menin with DNA methyltransferase 1 (Dnmt1) competitively pulled down Dnmt1 from p18 and p27 promoters, leading to the downregulation of DNA methylation levels. Moreover, menin expression was suppressed by Dnmt1 downstream of the Hedgehog signaling pathway, and menin overexpression strongly antagonized the promotion effect of hedgehog signaling on pancreatic cancer cell proliferation. Taken together, the interaction between menin and Dnmt1 reversibly regulates pancreatic cancer cell growth downstream of Hedgehog pathways with complex mutual modulation networks, suggesting that the Hedgehog/Dnmt1/menin axis is a potential molecular target for pancreatic cancer therapy.